Simultaneous Estimation of Mefenamic Acid and Drotaverine Hydrochloride in Tablets by High Performance Thin Layer Chromatography - N. Maliye, Amit; G. Walode, Sanjay; V. Kasture, Avinash; G. Wadodkar, Sudhir (Asian Journal of Chemistry, 2010)
A simple, rapid, sensitive high performance thin layer chromatographic method was developed and validated for simultaneous estimation of mefenamic acid and drotaverine hydrochloride in tablets. It was performed on TLC plate precoated with silica gel 60GF254 as a stationary phase and methanol :4 toluene: triethylamine (1:7.5:0.2) as mobile phase and the quantitation was carried out at 241 nm in absorbance mode. The Rf values were found to be 0.30 and 0.47 for mefenamic acid and drotaverine hydrochloride, respectively. The results were calculated as percentage of stated amount in each average weight of the tablet in marketed formulation and were found to be 99.45 ± 0.76, 99.29 ± 0.20 by peak height and 100.00 ± 1.18, 101.04 ± 0.77 by peak area. The method was validated in terms of accuracy, precision, specificity, ruggedness and linearity in the range of 3800–8400 ng for mefenamic acid and 1200–2700 ng for drotaverine hydrochloride. The recovery studies were carried out by standard addition method and % recovery was found to be 100.39% ± 1.30 and 99.50% ± 1.25 for mefenamic acid and 99.08% ± 0.61 and 100.86% ± 0.66 for drotaverine hydrochloride, respectively.